2022
DOI: 10.3892/mmr.2022.12743
|View full text |Cite
|
Sign up to set email alerts
|

Roles of circular RNAs in osteogenic differentiation of bone marrow mesenchymal stem cells (Review)

Abstract: Bone marrow mesenchymal stem cells (BMSCs) can differentiate into osteoblasts, chondrocytes, adipocytes and even myoblasts, and are therefore defined as pluripotent cells. BMSCs have become extremely important seed cells in gene therapy, tissue engineering, cell replacement therapy and regenerative medicine due to their potential in multilineage differentiation, self-renewal, immune regulation and other fields. Circular RNAs (circRNAs) are a class of non-coding RNAs that are widely present in eukaryotic cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…They are a popular choice in research related to BTE owing to their strong proliferation and osteogenic differentiation abilities. 57,58 The findings of the CCK-8 experiments in this study revealed that the different concentrations of SHSS extracts did not negatively impact cell proliferation, similar to the results of the control group. Furthermore, the live/dead staining of cells cultured on the surface of the scaffold revealed that BMSCs exhibited normal proliferation with a favorable morphology during incubation.…”
Section: Discussionsupporting
confidence: 78%
“…They are a popular choice in research related to BTE owing to their strong proliferation and osteogenic differentiation abilities. 57,58 The findings of the CCK-8 experiments in this study revealed that the different concentrations of SHSS extracts did not negatively impact cell proliferation, similar to the results of the control group. Furthermore, the live/dead staining of cells cultured on the surface of the scaffold revealed that BMSCs exhibited normal proliferation with a favorable morphology during incubation.…”
Section: Discussionsupporting
confidence: 78%
“…Extensive research has demonstrated the crucial involvement of circRNAs in bone metabolism-related diseases. 34 , 35 , 36 For instance, circ_0005752 has been shown to promote the osteogenic differentiation of adipose-derived stem cells, 37 while circRNA AFF4 activates the SMAD1/5 pathway to enhance the osteogenic differentiation of BMSCs. 38 Notably, circRNAs possess the ability to act as "molecular sponges" by sequestering miRNAs and inhibiting their function.…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory activities of circRNAs on miRNAs targeting Wnt/β-catenin-associated genes have been documented in several studies carried out with bone marrow MSCs (BMSCs) [70,71] (Table 1, Figure 3, A). Microarray analysis performed to determine the circRNAome during BMSC osteoblast differentiation has indicated the simultaneous expression of circIGSF11 and downexpression of hsa-miR-199b-5p.…”
Section: Wnt/β-catenin Pathwaymentioning
confidence: 99%